Thwaites Glacier time series ice surface flow speeds at (107.09 W, 75.48 S) from January 2012 to December 2020 - Bevan, Suzanne; Luckman, Adrian; Benn, Douglas (NERC EDS UK Polar Data Centre, 2021)
A time series of surface ice flow speed at a point on Thwaites Glacier, West Antarctica. The point is on grounded ice and is upstream of a sub-shelf cavity on the west flank of the fast-moving core of Thwaites Glacier. There are a total of 589 points. First column = yyyy-mm-dd, second column = speed in kilometres per year. The work was funded by NERC projects NE/P011365/1 and NE/S006605/1. : From 2012 to 2014 speeds were measured using feature-tracking of TerraSAR-X image pairs separated by 11 days. TerraSAR-X images were supplied by DLR. Speeds from 2015 onwards were measured using feature-tracking of Sentinel-1A and Sentinel-1B images separated by 6 or 12 days. Sentinel images were supplied by ESA. : Feature tracking was carried out using Gamma Remote Sensing software 20190603. : All feature-tracked displacements were filtered twice: first by a signal to noise ratio based on the cross-correlation of image patches, and then according to deviation from the mean displacement within a neighbourhood. The displacements were converted from the SAR image geometry to ground range geometry, and the results geocoded using the RAMP DEM (Liu et al., 2015).